EFEKTIVITAS MODEL DISCOVERY LEARNING BERBANTUAN PhET TERHADAP PROSES DAN HASIL BELAJAR SISWA - Maria Winda Galla; Marianus; Ferdy Dungus (Charm Sains: Jurnal Pendidikan Fisika, 2020)
Physics learning process still has many obstacles including the limitations of the use of practicaltools in the learning process, teachers in teaching using methods that are not in accordance with thecharacteristics of the material being taught. This study aims to determine the effectiveness of thePhET Media Media-Aided Discovery Learning model on student learning processes and outcomes.This research is an experimental research with one group pretest & postest design. The populationis all students of class X1 at SMAN 1 Remboken 2019/2020, and the sample is class XI IPA 2. Dataanalysis of science process skills has fulfilled both good and very good categories (66% -79%) and(80% -100%). The average student learning outcomes seen from the posttest = 80 which is greaterthan the KKM value. T-test results obtained t-count = 3.093 and t-table = 2.051 with a significancelevel of 5%. Therefore tcount> table then: H1 is accepted and H0 is rejected, it can be concludedthat the Discovery Learning model with the help of the PhET simulations media is effective againstthe process and student learning outcomes at SMAN 1 Remboken on the kinetic gas theory material.